Pengembangan Media Pembelajaran Berbasis Wordwall untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPA Sub Tema Ekosistem pada Siswa Kelas 5 di SDN 19 Muara Telang - Zahra, Aprilia; Yusuf, Yusni Arni; Anggraini, Novita Citra; Amelia, Suci (LPPPI Publishing, 2024)
The aim of this research is to use Wordwall as a learning tool to improve students' understanding of Natural Sciences (IPA), with special emphasis on the ecosystem subtheme. Grade 5 students at SDN 19 Muara Telang use this media as an interactive learning alternative that is interesting and easy to use. This research uses research and development (R&D) methods using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). 30 students in grade 5 were research subjects. This research shows that the use of Wordwall media can increase students' understanding of ideas. ecosystem. The pretest and posttest results which increased by an average of 25% show this improvement. This media also received positive responses from students and teachers, who found it interesting, interactive and easy to understand. Therefore, the development of Wordwall-based learning media can be recommended as a way to improve the quality of science learning, especially the ecosystem sub-theme.